2016
DOI: 10.1002/2016gl070620
|View full text |Cite
|
Sign up to set email alerts
|

Doubling of annual ammonia emissions from the peat fires in Indonesia during the 2015 El Niño

Abstract: In the autumn of 2015, thousands of square kilometers of forest and peatlands in Indonesia went up in flames. Among the primary species emitted by fires, ammonia (NH3) is of special relevance for air quality. Here we derive daily and total NH3 emission fluxes over the affected area using satellite measurements for the years 2008–2015. The 2015 fires emitted an estimated 1.4–8.2 Tg of NH3 (with a maximum of 0.06–0.33 Tg d−1). On an annual basis, the 2015 NH3 emissions are a factor 2–3 larger than in the previou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(58 citation statements)
references
References 38 publications
0
56
0
1
Order By: Relevance
“…1, panel b) are only found close to the source of emissions due to the relatively short lifetime of NO 2 (of a few hours; Schreier et al, 2014b). With a lifetime of typically 12-36 h in the studied regions (Dentener and Crutzen, 1994;Aneja et al, 2001;Whitburn et al, , 2016a, NH 3 is more likely to be transported over longer distances. This can be seen on the NH 3 -CO correlation map on which positive correlations are also found over seas downwind of the source areas.…”
Section: Selection Of the Areas And Biomes And Calculation Of The Er mentioning
confidence: 90%
See 1 more Smart Citation
“…1, panel b) are only found close to the source of emissions due to the relatively short lifetime of NO 2 (of a few hours; Schreier et al, 2014b). With a lifetime of typically 12-36 h in the studied regions (Dentener and Crutzen, 1994;Aneja et al, 2001;Whitburn et al, , 2016a, NH 3 is more likely to be transported over longer distances. This can be seen on the NH 3 -CO correlation map on which positive correlations are also found over seas downwind of the source areas.…”
Section: Selection Of the Areas And Biomes And Calculation Of The Er mentioning
confidence: 90%
“…With a contribution estimated to be about 13 % (Galloway et al, 2004) of the total emissions, biomass burning is believed to be the second most important source of NH 3 after agriculture. From previous studies, it has been shown that biomass burning could significantly affect NH 3 concentrations in the atmosphere, especially in the tropics but also at higher latitudes (e.g., Bouwman et al, 1997;Coheur et al, 2009;Adon et al, 2010;Alvarado et al, 2011;Shephard et al, 2011;Adon et al, 2013;R'Honi et al, 2013;Whitburn et al, , 2016aBenedict et al, 2017;Warner et al, 2017). Excess NH 3 in the environment is of great concern since it is responsible for many environmental is-sues such as eutrophication of terrestrial and aquatic ecosystems, soil acidification, and loss of plant diversity (Aneja et al, 2001;Erisman et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…We gained the data upon request from the Atmospheric Spectroscopy Group at Université Libre De Bruxelles (http://www.ulb.ac.be/cpm/atmosphere.html). These data can be gridded on 0.1 • latitude × 0.1 • longitude (Dammers et al, 2016), 0.25 • latitude × 0.25 • longitude (Whitburn et al, 2016a) and 0.5 • latitude × 0.5 • longitude (Whitburn et al, 2016b) or even coarser resolutions depending on the usage of the data. For IASI NH 3 , we firstly divided China into a 0.5 • latitude × 0.5 • longitude grid.…”
Section: Satellite Observationsunclassified
“…The emissions from Indonesian peat fires during the 2015 El Niño were estimated using mean EFs calculated in this study for an estimated burned area of 8.5× 10 5 ha (Whitburn et al, 2016), an average burning depth of 34 ± 12 cm (calculated during this study; Stockwell et al, 2016), and a peat bulk density of 0.120 ± 0.005 g cm −3 (Konecny et al, 2016). The uncertainty of the estimated value is propagated using standard deviation of the mean EFs, burn depth, and peat bulk density.…”
Section: Emission Estimates From 2015 Indonesian Peat Firesmentioning
confidence: 99%